2018
DOI: 10.29252/johe.7.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal communication skills and its association with personality dimensions of nurses in Rafsanjan University of Medical Sciences, Iran, in 2015

Abstract: Article Info Background: Communication is a necessity of social life which is very important in health care settings due to the type of work and clients. The aim of this study was determine the association between interpersonal communication skills (ICSs) and personality dimensions of nurses working in Rafsanjan University of Medical Sciences. Materials and Methods: In this descriptive study, 223 nurses were selected by stratified random sampling method and they completed the Burton ICSs and the Revised NEO Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Accordingly, it results in comprehensive care along with the identification of needs and changes, continuous care, trust and intimacy, mutual therapeutic communication, experiencing recovery and wellbeing during illness, and improving patient's quality of life (Strandås & Bondas 2018). However, according to a study (Agha Mohammad Hasani et al 2018), >85% of nurses fail to establish proper interpersonal communication, and their ability to communicate, listen and express is moderate. A study on the quality of care in hospitalized patients indicated that most of the patients' dissatisfaction concerns nurse-patient communication and providing an insufficient and unclear explanation about the tests and treatment process (Karaca & Durna 2018).…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Accordingly, it results in comprehensive care along with the identification of needs and changes, continuous care, trust and intimacy, mutual therapeutic communication, experiencing recovery and wellbeing during illness, and improving patient's quality of life (Strandås & Bondas 2018). However, according to a study (Agha Mohammad Hasani et al 2018), >85% of nurses fail to establish proper interpersonal communication, and their ability to communicate, listen and express is moderate. A study on the quality of care in hospitalized patients indicated that most of the patients' dissatisfaction concerns nurse-patient communication and providing an insufficient and unclear explanation about the tests and treatment process (Karaca & Durna 2018).…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Goleman lebih jauh berpendapat bahwa orang yang cerdas secara emosional bisa melakukan penanganan yang efektif bagi orang lain, secara emosi dengan memanipulasi situasi, bahasa tubuh dan percakapan untuk mengelola dan mengatur emosi orang lain ke suatu arah, menguntungkan bagi situasi. Dalam praktiknya, kecerdasan emosional dapat menjadi kompetensi, kemampuan dan sifat kepribadian dari seorang karyawan untuk memahami, memanfaatkan, dan mengelola emosi secara efektif (Goleman, 2018;Hasani et al, 2018).…”
Section: Pembahasan Hubungan Kecerdasan Emosional Perawat Terhadap Komunikasi Interpersonal Dengan Pasienunclassified
“…One of the most important factors affecting the increase of client satisfaction is the way health care providers communicate and the ability to communicate properly with clients. (11) In this regard, various studies have shown that interpersonal communication between HCP is the most important factor affecting people's satisfaction with health care systems (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%